Nursing vaccine mandates: Ethically justified, an infringement on autonomy, or both? - Charles, Christopher M. (Nursing ethics, 2025)
After almost a year and a half of the COVID-19 pandemic, many healthcare institutions in the United States announced that they would mandate COVID-19 vaccination, with medical and religious exceptions, as a term of employment. The mandates resulted in widely publicized protests from hospital staff, including some nurses, who argued that these medical institutions violated the ethical principle of autonomy. As the world enters the “post-pandemic period,” decisions such as these, made during times of crisis, must be reviewed to provide clarity for when the next pandemic occurs. In this paper, we support the argument that such mandates are ethically justifiable. We explore the framework of objections that were brought forward by dissenters of this vaccine mandate. Next, we provide an analysis of conflicting ethical principles present when such mandates were deployed. Utilizing the American Nurses Association’s Code of Ethics for Nurses, notably provisions 2, 3, and 6 we argue that it is an ethical duty of the nurse to be vaccinated. Specifically, we turn to provision two, which most explicitly underscores the necessity of vaccination as a function of the nurse’s primary commitment to the patient. Next, we highlight the International Council of Nurses Code of Ethics which provides similar guidance internationally. Finally, we examine the applicability of the principles of public health, care ethics, and the nursing role as frameworks to underpin such mandates both for the current and for potential future pandemics, arguing that the nurse’s ethical duty to be vaccinated spans these contexts.